EXPLORING TEACHER’S ANXIETY IN USING ENGLISH AND THEIR MANAGEMENT STRATEGIES AT BILINGUAL SCHOOL - Mardhiyah Muchtar; La Ode Sidu Marafad; Kamaluddin Kamaluddin (Journal of Language Education and Educational Technology (JLEET), 2020)
Psychological influence is a never-ending aspect that can not be separated from language teaching and learning, and Foreign Language Teaching Anxiety is one of those psychological hindrances. This study was aimed to find out the causes of foreign language teaching anxiety (FLTA) of teachers in bilingual school, the effects, how the teachers deal with their anxieties, and school support in helping the teachers. This research employed qualitative research, and using a close-ended questionnaire, interview, and observations as sources of the data. The participants were all teachers of Lazuardi Ibnu Sina Elementary School which consists of 10 teachers (6 Homeroom Teacher and 4 Subject Teachers). The results indicated that the majority of teachers fear negative evaluations from the students and supervising teachers.  It also showed that the teachers used professional, personal, and social strategies to manage their anxieties.  As for the effects, most of the teachers think that teacher anxiety will affect their image in front of students and students will not get enough exposure to English. In light of these findings, it also showed that bilingual school should provide more English Classes and English Day for their teachers and school in order to improve their English skills and manage their teaching anxieties.